Pattern of Thyroid Swelling – A Histopathological Study (Sir Salimullah Medical College Journal, 2022)
Background: This is a cross sectional study. The purpose of the study was to determine the histopathological pattern in Thyroid swellings. The study was done in the department of Otolaryngology and Head-Neck Surgery, Sir Salimullah Medical College Mitford Hospital, Dhaka from December 2015 to December 2016. Fifty patients of Thyroid swelling were studied by detailed history, clinical examination, thyroid hormone assay, ultrasonography, Thyroid scan, FNAC and Histopathological examination.Results: In this study it was found that Goitre is predominant in female. Among the 50 cases nodular colloid goitre was found in 25 cases in FNAC suspicious cell for malignancy in 2 cases, follicular neoplasm in 11 cases & malignancy in 11 cases. Histopathology reports were obtained in all cases. Histopatholgical findings of the swelling shows that 42.0% of the swelling are Nodular colloidal goiter and 24.0% tumor are follicular adenoma and thyroiditis was found in 8 % cases. Among malignancy papillary carcinoma was in 20% cases while folicullar carcinoma and medullary carcinoma was 4% and 2% respectively. No case of anaplastic carcinoma and lymphoma was found. Proportion of papillary carcinoma was highest in the age group 30 years and below and proportion of follicular carcinoma was highest in age group above 50 years patients while nodular colloidal goiter was highest in age group 31 to 50 years patients.Thyroiditis was highest in the age group 31 to 50 year’s patients and follicular adenoma was highest in the age group above 50 years patients. Proportion of follicular carcinoma (25.0%) and medullary carcinoma (12.5%) was higher in male patients than female. On the other hand proportion of nodular colloidal goiter (40.5%), thyroiditis (9.5%), papillary carcinoma (21.4%) and follicular adenoma (26.2%) was higher in female patients than male.Conclusion: Clinical evaluation of goiter should be thorough, and use all means especially histopathologic study of the specimens to arrive at a definitive diagnosis as thyroid carcinoma is not uncommon.Sir Salimullah Med Coll J 2022; 30: 75-82